Fabrication and Characterization of Graphene Oxide Doped SU-8 Polymer Waveguide - Ibrahim, Mohd Haniff; Salim, Mohd Rashidi; Mohd Noor, Muhammad Yusof; Mohd Kassim, Norazan (ELEKTRIKA- Journal of Electrical Engineering, 2018)
In this paper, graphene oxide (GO) was doped into SU-8 polymer to examine the functionalities of polymer waveguide material via dopant inclusion. In material preparation, step by step processes starting from cyclopentanone mixing will be explained. It is shown that doped material's refractive index can be tailored by having different weight percentage of GO. Finally, a single mode ridge waveguide loss of GO doped SU-8 has been characterized to be 1.9 dB/cm at 1550 nm wavelength.